Bacterial Infestation in Different Fish at Rajshahi (Journal of Science Foundation, 2013)
The present study was carried out from July 2005 to June 2007 and diseased freshwater fishes were collected from different water bodies and fish landing centre of three study areas, namely City Corporation area, Rajshahi; Paba upazila and Charghat upazila, Rajshahi. In the present study the load of bacteria in lesion, liver and kidney of H. molitrix showed considerable variation in different months during the study period. Monthly variation of bacterial load in body lesion varied from 3.17×104 CFU/g (July05) to 2.13×107 CFU/g (March07), in liver it varied from 7.17×103 CFU/g (July05) to 5.13×106 CFU/g (March06) and in kidney it varied from 5.87×103 CFU/g (July05) to 6.33×105 CFU/g (March06). From two years observation, monthly variation of bacterial load in 3 sampling ponds were varied from 4.00×106 CFU/ml (June07) to 3.93×107 CFU/ml (July05) in case of pond-1. In pond-2 bacterial load varied from 1.27×106 CFU/ml (May07) to 5.33×107 CFU/ml (September06). In pond-3 the bacterial load varied from 2.10×106 CFU/ml (June07) to 2.10×108 CFU/ml (July06). DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14650 J. Sci. Foundation, 9(1&2): 77-84, June-December 2011